The relationship between workplace incivility and organisational citizenship behaviour in private and public sector , Kota Kinabalu, Sabah - Li, Wen Jing (2011)
The aim of this study is to determine the relationship between workplace incivility and organisational citizenship behaviour. Workplace incivility is the independent variable while organisational citizenship behaviour is the dependent variable. Job satisfaction is introduced as a mediator to throw a new perspective to the relationship between workplace incivility and organisational citizenship behaviour. Data were collected from 170 employees working in private and public sectors in Kota Kinabalu, Sabah. Multiple linear regression results indicated there is no significant direct relationship between workplace incivility (supervisor incivility and co-worker incivility) and organisational citizenship behaviour, even though the relationship Is negative. However, the results indicated that workplace incivility affect organisational citizenship behaviour via job satisfaction. Only supervisor incivility has negative effect on job satisfaction while co-worker incivility has no influence; and job satisfaction has positive effect on organisational citizenship behaviour.